Implementation of Learning Models With ASIK Concepts to Improve Learning Achievement in Pancasila Education in The Digital Era - Purnami, Ni Ketut Ayu; Temon Astawa, I Nyoman (Jayapangus Press, 2025)
The application of the problem-based learning model with the ASIK concept aims to improve student learning achievement in Pancasila Education subjects in the digital era. For this reason, in the test, a class was taken as a sample, namely class XII C at SMA Negeri 2 Bangli in Semester 1 of the 2024/2025 academic year. This research was carried out using qualitative methods, by collecting data through tests, observations, and interviews which were analyzed descriptively. This research was carried out in two stages, by making improvements to the learning steps using the ASIK concept until finally a significant increase in student learning achievement was obtained. From this research, it can be concluded that the implementation of the learning model with the ASIK concept can improve learning achievement in Pancasila Education in the digital era. In this way, students can use their smartphones for meaningful learning activities.